DETERMINING THE PROFITABILITY OF PT. ASURANSI JIWA SYARIAH JASA MITRA ABADI TBK. (JMAS) PERIOD 2017 – 2024 - Muhammad Farhan zuhdi; Nurwani; Khairina Tambunan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research seeks to examine the effect of contribution income, claim expenses, and risk-based capital on PT's profitability. Asuransi Jiwa Mitra Syariah Tbk. (JMAS). In contemporary times, the demand for financial security is growing, leading insurance to have a significant role in handling the risks faced by clients. This research employs a quantitative approach utilizing secondary data derived from the company's yearly financial reports for the years 2017-2024, comprising a population and sample of 32 data points, with the sampling method being a saturated sample. The study's results indicate that contribution income has a negligible impact on profitability, as claim burden follows contribution income. At the same time, claims costs greatly influence profitability. Conversely, risk-based capital (RBC) has minimal impact on profitability, underscoring the necessity of effective fund management. This conclusion indicates that these elements need to be effectively managed to enhance the financial performance of Islamic insurance firms. This study aims to offer guidance for management and stakeholders in making strategic decisions to enhance profitability